2013
DOI: 10.1155/2013/212830
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological Studies on Stunting Syndrome in Broilers, Lahore, Pakistan

Abstract: Runting stunting syndrome (RSS) is a multifactorial disease with many names and faces that had caused considerable economic losses to poultry through reduced uniformity, reduced livability, decreased body weights, elevated feed conversions, and many secondary diseases. The aim of the current study was to evaluate the effect of stunting syndrome on histopathology in chicks (n = 120) of different ages collected from nine different farms. Grouping was done on the basis of age (G1 = 1–10 days, G2 = 11–20 days, G3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

10
11
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 22 publications
10
11
0
Order By: Relevance
“…In order to assess the role of viruses in naturally occurring RSS, the clinical features and histopathology were characterized, NGS was used to identify viral reads associated with RSS, and ISH was used to determine the location of virus in affected and unaffected intestinal tissues. Consistent with previous reports, 12,25,35 poor growth and feed conversion were the major clinical signs in the present study. Dilated and necrotic crypts with villous atrophy and mixed inflammatory infiltrates were histologically identified throughout all sections of the small intestine.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In order to assess the role of viruses in naturally occurring RSS, the clinical features and histopathology were characterized, NGS was used to identify viral reads associated with RSS, and ISH was used to determine the location of virus in affected and unaffected intestinal tissues. Consistent with previous reports, 12,25,35 poor growth and feed conversion were the major clinical signs in the present study. Dilated and necrotic crypts with villous atrophy and mixed inflammatory infiltrates were histologically identified throughout all sections of the small intestine.…”
Section: Discussionsupporting
confidence: 93%
“…Other lesions of RSS include degeneration and vacuolation of pancreatic acinar cells with fibrosis, proventriculitis with glandular degeneration and infiltrate of macrophages and lymphocytes, 35,40 and atrophy of cloacal bursa. 35 These lesions were absent in the current study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that birds with this syndrome exhibited diminished pancreatic amylase activity and changes in pancreatic protease levels (Szabo et al 1989). Histological studies of pancreatic lesions in broilers with RSS revealed fibrosis, inflammation, vacuolar changes in the exocrine compartment, degeneration of acinar cells and loss of zymogen granules (Qamar et al 2013). In pigeons, exocrine pancreas disease produced voluminous, coloured faeces and weight loss (Amann et al 2006), and when aflatoxins are present in the diet, histological changes in the pancreas are observed, together with effects on performance and nutrient absorption (Marchioro et al 2013).…”
Section: Discussionmentioning
confidence: 87%
“…The syndrome is sometimes characterized by the more chances of occurrence (2-15%) in birds of two weeks of age with reduced body weight and poor feathering (Smart et al, 1988). There are large number of possible reasons for RSS including some management issues, environmental challenges, infectious diseases, faulty poultry genetics, nutrition and feeding, and perhaps some other reasons and/or any possible combinations of all these (Zavalla and Sellers, 2005;Qamar et al, 2013). Some particular chicks were observed more susceptible than others and the males were found affected much severely than females (Rebel et al, 2006).…”
mentioning
confidence: 99%